One health approach to identify research needs on Rhipicephalus microplus ticks in the Americas - Estrada-Peña, Agustín; Rodriguez Mallon, Alina; Bermudez, Sergio; Domingos, Ana; Estrada Garcia, Mario Pablo; Labruna, Marcelo B.; Merino, Octavio; Nava, Santiago; Tarragona, Evelina Luisa; Venzal, José Manuel; de La Fuente, José; Mosqueda, Juan; et al. (MDPI, 2022)
We aim to provide a harmonized view of the factors that affect the survival and promote the spread of R. microplus in the Neotropics, approaching its different facets of biology, ecology, distribution, and control. We review the interactions among environmental niche, landscape fragmentation, vegetal coverage (abiotic traits), and the biotic aspects of its ecology (abundance of domesticated or wild competent hosts), proposing emerging areas of research. We emphasize a holistic view integrating an economically and ecologically sustainable control of infestations and transmitted pathogens by R. microplus in the Neotropics. Examples of research link the trends of climate, the composition of the community of hosts, the landscape features, and a tailored management based on ecological grounds. Our view is that factors driving the spread of R. microplus are complex and deeply interrelated, something that has been seldom considered in control strategies. The effects of climate may affect the dynamics of wildlife or the landscape composition, promoting new patterns of seasonal activity of the tick, or its spread into currently free areas. In this paper we encourage a One Health approach highlighting the main aspects governing the components of the tick’s life cycle and its interactions with livestock and wild animals.